Impact of Fluoride on the Enamel of Deciduous and Permanent Teeth With Reference to the Intake of Fluoride via Drinking Water and Tea - Verma, Dr. Rajesh; Yadav, Naveena (American Journal of Bioscience and Clinical Integrity, 2025)
Fluoride plays a crucial role in promoting dental health by enhancing enamel resistance through remineralization and by inhibiting demineralization. This study aimed to evaluate the impact of fluoride exposure from two common dietary sources—drinking water and black tea—on the enamel of both deciduous and permanent teeth. A total of 112 extracted human molars (56 deciduous and 56 permanent) were used, divided into four groups based on exposure: fluoridated water, brewed black tea, water with topical fluoride gel, and tea with topical fluoride gel. Over a 30-day period, teeth were immersed daily in the respective solutions, and weekly topical fluoride application was administered to relevant groups. Fluoride concentrations in beverages were assessed using the ion-selective electrode (ISE) method, with tea samples showing significantly higher fluoride content (1.5–3.0 ppm) compared to bottled drinking water (0.1–0.5 ppm). Post-exposure analysis using Scanning Electron Microscopy with Energy Dispersive X-ray (SEM-EDX) revealed a marked increase in enamel fluoride levels across all groups, with the highest uptake observed in tea-exposed deciduous teeth. Structural differences—such as higher porosity and thinner enamel in deciduous teeth—contributed to their greater fluoride absorption efficiency. Findings suggest that while both systemic (ingestion) and topical fluoride sources are effective in enhancing enamel resistance, excessive intake may elevate the risk of dental fluorosis, particularly in children. Therefore, it is recommended that fluoride levels in drinking water and tea be monitored regularly, and that fluoride use in pediatric populations be carefully managed. This study underscores the need for balanced fluoride exposure to optimize oral health outcomes across all age groups.